2001
DOI: 10.1161/01.cir.103.11.1535
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis After Aortic Valve Replacement With a Bioprosthesis

Abstract: Background-Bioprostheses are widely used as an aortic valve substitute, but knowledge about prognosis is still incomplete. The purpose of this study was to provide insight into the age-related life expectancy and actual risks of reoperation and valve-related events of patients after aortic valve replacement with a porcine bioprosthesis. Methods and Results-We conducted a meta-analysis of 9 selected reports on stented porcine bioprostheses, including 5837 patients with a total follow-up of 31 874 patient-years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…6,18,19 In the context of surgical AVR, there is a wide range in the reported incidences of valve thrombosis from as low as 0.03% to 5.0%. [8][9][10][11][12] These reported incidences concur with the one from our study, despite the fact that TAVI patients have more comorbidities predisposing them to prothrombotic states. This suggests that the bioprosthetic material inserted in the aortic valve position rather than other predisposing factors, plays the major role in valve thrombosis.…”
Section: Prevalence and Timing Of Thv Thrombosissupporting
confidence: 91%
See 1 more Smart Citation
“…6,18,19 In the context of surgical AVR, there is a wide range in the reported incidences of valve thrombosis from as low as 0.03% to 5.0%. [8][9][10][11][12] These reported incidences concur with the one from our study, despite the fact that TAVI patients have more comorbidities predisposing them to prothrombotic states. This suggests that the bioprosthetic material inserted in the aortic valve position rather than other predisposing factors, plays the major role in valve thrombosis.…”
Section: Prevalence and Timing Of Thv Thrombosissupporting
confidence: 91%
“…6,7 The reported incidences of valve thrombosis postsurgical AVR using bioprostheses ranges widely from as low as 0.03% to 5.0%. [8][9][10][11][12] Conversely, data on transcatheter heart valve (THV) thrombosis are scarce and restricted to several case reports and small case series. [13][14][15] A recent meta-analysis on clinical outcomes after TAVI using Valve Academic Research Consortium definitions reported a 1.2% pooled estimated incidence of THV thrombosis.…”
Section: Latib Et Al Thv Thrombosismentioning
confidence: 99%
“…32 First, after the determinants and events of interest have been specified, the parameters of their associations should be assessed. The value and uncertainty of the parameters (β coefficients) can be estimated using various approaches.…”
Section: Battes L Et Almentioning
confidence: 99%
“…Also, microsimulation allows changing hazards over time. 32 Hazards may change over time because provides a useful tool for modeling processes at the population level, its properties limit studying the remaining lifetime of an individual patient. Microsimulation, also termed discrete-event simulation, Monte Carlo simulation or dynamic risk modeling, offers a better solution for this situation.…”
mentioning
confidence: 99%
“…Prosthetic valve endocarditis (PVE), which affects as many as 3.4 % of patients in the year following surgery and 1 % annually thereafter (Puvimanasinghe et al, 2001), is frequently associated with reoperation and significant mortality. Fungal PVE can occur early (within 60 days of surgery) or late (after 60 days), but an early occurrence is generally not seen in the absence of pre-operative fungal infections.…”
Section: Introductionmentioning
confidence: 99%